PENGARUH POLA JARAK TANAM DAN BERBAGAI DOSIS PUPUK NPK TERHADAP PERTUMBUHAN DAN HASIL TANAMAN PADI (Oryza sativa L) - suartana, I Ketut; Monde, Anthon; Hasanah, Uswah; Prahastuti, Sri Wahida (AGROTEKBIS, 2018)
This study aimed to determine the effect of plant spacing and various amounts/ratios of NPK fertilizerson the growth and nitrogen uptake of wetland rice (Oryza sativa L.) varieties IR 64. The experimental design was a two-factorial Split Plot in a Randomized Block design. Two plant spacing types as the main plots i.e. symmetrical (s1) and Legowo (s2) were applied. The various ratiosof NPK fertilzers as the sub plots consisted of 200 kg :75 kg : 50 kg per ha (p1), 250 kg : 100 kg :75 kg per ha (p2), 300 kg :125 kg :100 kg per ha (p3), and 350 kg :150 kg : 125 kg per ha (p4). There were eight combination treatments and each had three replicates.The results showed that the interaction between the plant spacing and the NPK fertilizer significantly affect tiller number, panicles per clump and nitrogen uptake. Highest tiller number, panicles per clump and nitrogen uptake were found in the s2p4 treatment which were 67.50, 30.50 and 125.60 kg, respectively, whereas lowest ones were in the s1p1 which were 26.50, 13.52 and 51.66 kg, respectively.